Studies on Toothbrushes Contaminated by Diabetic and Non-Diabetic Patients and it’s Disinfection Procedures: A Cross-Sectional Study (Update Dental College Journal, 2025)
Background: Toothbrushes act as reservoirs for microbial contamination and are essential for maintaining human oral hygiene.  Diabetic individuals are at a higher risk of contamination due to compromised immune responses. This study evaluates bacteria contamination and the efficacy of different disinfection methods for toothbrushes used by diabetic and non-diabetic individuals.Methods: A cross-sectional study and clinical trial were conducted among 120 participants (60 diabetic and 60 nondiabetic). Used toothbrushes were collected and divided into control and experimental groups and subjected to disinfection using 2% chlorhexidine (CHX), 5% sodium hypochlorite (NaOCl), vinegar, and tap water. Bacterial cultures were performed using MacConkey agar and blood agar. Statistical analysis was performed using SPSS software (version 21).Results: Toothbrushes used by diabetic individuals exhibited significantly higher microbial contamination than those used by non-diabetic individuals. Here the most prevalent bacterial isolates were Streptococcus mutans (60% in diabetics vs. 46.6% in non-diabetics), Staphylococcus aureus (43.8% vs. 55%), Pseudomonas spp. (78.3% vs. 38.3%), and Escherichia coli (71.6% vs. 58.3%). Among the tested disinfectants, 5% NaOCl demonstrated the highest disinfection efficacy (100%), followed by 2% CHX (85%) and vinegar (65%). Tap water failed to reduce microbial load effectively (10%).Conclusion: Toothbrushes of diabetic individuals are significantly more contaminated than those of non-diabetic individuals, increasing the risk of oral and systemic infections. Disinfection with 5% NaOCl or 2% CHX effectively reduces microbial contamination and should be recommended as routine practice. Further studies are needed to explore additional disinfection methods and their long-term efficacy.Update Dent. Coll. j: 2025; 15(1): 28-32